Are we where we wanted to be? Modernist tendencies versus the postmodern reality of archaeology. Some remarks on the methodology of archaeologists at Adam Mickiewicz University in Poznań - Minta-Tworzowska, Danuta (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
This article attempts to define the place where the Poznań University’s methodology of archaeology finds itself. The question contained in the title – a are we where we wanted to be? – requires an answer that considers the extent to which the modernist assumptions of archaeo- logy, in which we grew up, have been fulfilled, and to what extent we function in the postmodern world. The article presents the rationale for this methodology, showing some variation in the views of its representatives, starting with the founder of the school, Jan Żak, through his stu- dents to the next generation. Recognizing the polyphonic nature of this scholarship, an attempt was made to group these studies into specific issues, which are: reflection on the methodology and theory of archaeology; its inspirations and proposals; relations between theory, methods, and practice; issues of archaeological sources as ones reflecting methodological discussions in the diachronic approach; the past explored in the present; emerging fields of research such as landscape studies; and social archaeology, initiated at Adam Mickiewicz University with the work of Ciesielska on social theory. For many years, the concept of social archaeozoology has also been developed, and studies on memory, identity, children and childhood, among others, have been conducted. The broadening of research fields is an unquestionable achievement of the postmodern (post-processual) as well as post-postmodern reorientation, marking the world in which we function.
Keywords: methodology; theory of archaeology; postmodern